A hospital recreation room quality improvement intervention. Issue 4 (13th May 2019) - Dolan, Lorraine; Kane, Maria; Timmins, Fiona; Prizeman, Geraldine; Dempsey, Orla
Abstract : Purpose: Patients with extended hospital admissions had no recreation facilities in the ward. They were often confined to spaces around their beds, using the ward corridor for rehabilitation. The purpose of this paper is to outline a quality improvement (QI) intervention-provision of a recreational space for long-stay patients. Design/methodology/approach: An exploratory quantitative pre-, post-test design was utilised, and executed in three phases: patients, visitors and staff survey to explore recreation and comfort needs and preferences; store room refurbishment; and patient, visitor and staff satisfaction with the recreation room. Findings: Overall, 77 questionnaires were completed ( n =49 staff; n =28 patient/visitor). Almost two-thirds (64.7 per cent; n =11) of patients had a stay greater than six weeks. Insufficient private space and concerns about disturbing other patients were identified as barriers to taking part in activities. Consequently, a store room was refurbished as a recreation room (9.0 m × 6.0 m) and furnished in three distinct areas. Following refurbishment, over 90 per cent ( n =24) of respondents agreed that there was a suitable space where patients could "go and chat" and spend time with family and visitors or speak to the healthcare team. Practical implications: The physical environment in acute hospitals is seldom prioritised. Needs-based QI projects can improve patient hospital experiences. Originality/value: This case study highlights how nursing staff can be informed by patients' and families' needs and preferences, and initiate QI projects that improve patient hospital experiences.